HUBUNGAN FAKTOR PENGETAHUAN DAN PERILAKU TERHADAP LINGKUNGAN DALAM RANGKA PENCEGAHAN DBD PADA KELUARGA SISWA DI SMA NEGERI 1 BERASTAGI KECAMATAN BERASTAGI KABUPATEN KARO TAHUN 2017 - Perangin-Angin, Susanti br (Politeknik Kesehatan Kemetrian Kesehatan Medan, 2018)
Infectious diseases caused by viruses from the group of Arbovirosis group A and B problematic in Indonesia are Dengue Hemorrhagic Fever (DHF). The disease is transmitted by mosquito vector bites. This disease not only often cause outbreaks but also cause adverse social and economic impact. Social losses that occur, among others, caused panic in the family, the death of family members, and diminished life expectancy of the population. In 2015, there were recorded 126,675 DHF patients in 34 provinces in Indonesia, and 1,229 of them died. The number is higher than the previous year of 100,347 people with DHF and as many as 907 patients died in 2014. This can be caused by climate change and low awareness to maintain environmental cleanliness. This research is analytic observational with cross sectional approach that aims to know the Factor of Knowledge and Environment to the action of Dengue Prevention on Family Students in SMA Negeri 1 Berastagi Sub District Berastagi Regency of Karo Year 2017, with method used in sampling is non prababiliy sampling that is sampling quota (Quota sampling) is a sampling technique based on the fulfillment of the specified samples. To determine the representativeness of the sample to the population determined sample of 300 students taken in class 11 as many as 130 students, grade 12 as many as 170 students. The results of this study indicate that the level of knowledge of respondents is generally good that is equal to 72%, while the actions of respondents in the category of less that is equal to 64.3% and the environment included in the category of less that is equal to 51,7%. Result of analysis of knowledge and environment relationship with student action about DHF in order to prevent DBD in family of student in SMA Negeri 1 Berastagi Sub District Berastagi Regency of Karo. Based on hypothesis test using chi square test known that knowledge variable do not have significant relation to environment at p.value 0,992. And analysis result of relation between student action variable about DHF has no significant relation to student environment at p.value 0,046. This research can be concluded that knowledge about DHF is good but action and environment in order to prevent DHF less. In this research, it is advisable to keep the environment cleaner in order not to become Aedes aegypti mosquito breeding media that is in the form of mosquito nest eradication (PSN), fogging, abatization, 3M implementation (drain, cover and bury). In every health problem including in effort of DHF, Behavioral factors always play an important role. Attention to behavioral factors is just as important as attention to environmental factors, especially in terms of disease prevention efforts.